False positives, extrajudicial executions, homicide of a protected person, and forced disappearance in Colombia: Falsos positivos, ejecuciones extrajudiciales, homicidio de persona protegida y desaparición forzada en Colombia - Mejía Alfonso, Herbert Mauricio; Torregrosa Jiménez, Rodolfo Alfonso (Araucaria, 2024)
na